2017
DOI: 10.1057/s41304-016-0098-z
|View full text |Cite
|
Sign up to set email alerts
|

assessing party membership figures: the mapp dataset

Abstract: Assessments of party decline and decline of traditional forms of political participation often rely on the argument of party membership decline. Most studies analysing trends in party membership over time focus on aggregate country-level data at a few points in time. While they allow grasping general membership trends, they are not without shortcomings. This article presents the Members and Activists of Political Parties (MAPP) dataset related to the MAPP project. The dataset makes a large amount of data on pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Recent studies have reported a widespread dissatisfaction with the institution of representative democracy in advanced industrial democracies (Ferrín and Kriesi, 2016). Among the indicators of this critical stance are: declining party memberships (Van Haute et al, 2018), weaker party identification (Dalton, 2014), lower trust in parties (Dalton, 2004) and the rise of populist parties (Mudde, 2007;Kriesi and Pappas, 2015). This crisis proved to be fertile ground for a plethora of democratic innovations, ranging from participatory budgeting over deliberative mini-publics to direct legislation (Smith, 2009;Newton and Geißel, 2012;Elstub and Escobar, 2019).…”
Section: Elected Representatives and Democratic Innovationsmentioning
confidence: 99%
“…Recent studies have reported a widespread dissatisfaction with the institution of representative democracy in advanced industrial democracies (Ferrín and Kriesi, 2016). Among the indicators of this critical stance are: declining party memberships (Van Haute et al, 2018), weaker party identification (Dalton, 2014), lower trust in parties (Dalton, 2004) and the rise of populist parties (Mudde, 2007;Kriesi and Pappas, 2015). This crisis proved to be fertile ground for a plethora of democratic innovations, ranging from participatory budgeting over deliberative mini-publics to direct legislation (Smith, 2009;Newton and Geißel, 2012;Elstub and Escobar, 2019).…”
Section: Elected Representatives and Democratic Innovationsmentioning
confidence: 99%
“…The available data on party membership in Belgium based on parties' own records tends to confirm that mass membership has sharply declined in Belgium (van Haute & Paulis, 2017). In particular, the parties embodying the idea of pillar parties (Christian Democrats -CD&V and CDH, and Social Democrats -sp.a and PS) have seen their membership numbers decline drastically since the early 1990s (Table 1).…”
Section: Party Membership Levelsmentioning
confidence: 89%
“…The second part of the article investigates how parties are (still) representative of a specific subculture in Belgium by looking at both overlapping memberships and representativeness. We use several data sources: longitudinal party membership data (van Haute & Paulis, 2017) and party member surveys (listed on www. projectmapp.…”
Section: Introductionmentioning
confidence: 99%
“…Although this approach is certainly not new – Duverger (1964) and Key (1958) distinguished between different categories of party followers more than half a century ago – it has particular resonance today given the pervasive downward trend in ‘formal’ party membership (see e.g. Poguntke et al, 2016: 667; van Haute et al, 2017) and the organizational permeability noted above (Bolleyer, 2009; Katz and Mair, 2009). This decline is often characterized as reflecting membership organizations in crisis, rather than prompting a re-examination of the concepts of membership and partisan engagement – and whether the theoretical and empirical indicators that we rely on are still suitable.…”
Section: Understanding Partisan Activity: From Members To Supportersmentioning
confidence: 99%